Molecular characterization of resistance mechanisms in Pseudomonas aeruginosa isolates resistant to carbapenems - Shaaban, Mona; Al-Qahtani, Ahmed; Al-Ahdal, Mohammed; Barwa, Rasha (The Journal of Infection in Developing Countries, 2018)
Introduction: Emergence of carbapenem resistance in Pseudomonas aeruginosa increases the therapeutic dilemma. In this study, we investigated various mechanisms involved in the resistance of P. aeruginosa clinical isolates to carbapenems. Methodology: P. aeruginosa isolates were isolated from different clinical samples. The antimicrobial susceptibility was evaluated by disc diffusion method. Carbapenemases were detected among carbapenem resistant isolates. Expression level of mexB and oprD was determined by real-time PCR. Molecular relatedness among isolates was detected based on pulse-field gel electrophoresis (PFGE). Results: Ninety P. aeruginosa isolates were purified from clinical specimens. High levels of resistance to imipenem and meropenem were detected in 16 isolates. PCR analysis of carbapenemases indicated the prevalence of Verona integron-encoded metallo-beta-lactamase (VIM); four isolates produced only VIM enzymes (VIM-1 or VIM-2), while the remaining twelve co-produced both VIM-1 or VIM-2 and NDM enzymes. Additionally, real-time PCR analysis elucidated high expression levels of mexB in seven of the carbapenem resistant isolates and low expression of oprD in seven isolates. The identified carbapenem-resistant isolates were clustered into eleven PFGE profiles where clusters E1 and E2 involved isolates exhibiting multiple carbapenemase genes (blaNDM-1, blaVIM-1 and blaVIM-2). Conclusion: Various mechanisms underlying carbapenem resistance have been detected in our P. aeruginosa cohort of isolates. Emergence of P. aeruginosa as a reservoir of multiple carbapenemases is increasing over time limiting the treatment options to this serious infection. This increases the urgency for infection control practices to reduce the incidence of this infection.